How spirituality is understood and taught in New Zealand medical schools. Issue 1 (29th October 2013) - Lambie, D.; Egan, R.; Walker, S.; MacLeod, R.
Abstract Objectives: The objective of this research was to explore how spirituality is currently understood and taught in New Zealand Medical Schools. Methods: A mixed methods study was carried out involving interviews (n = 14) and a survey (n = 73). The first stage of the study involved recorded semi-structured interviews of people involved in curriculum development from the Dunedin School of Medicine (n = 14); which then informed a cross-sectional self-reported electronic survey (n = 73). Results: The results indicate that spirituality is regarded by many involved in medical education in New Zealand as an important part of healthcare that may be taught in medical schools, but also that there is little consensus among this group as to what the topic is about. Significance of results: These findings provide a basis for further discussion about including spirituality in medical curricula, and in particular indicate a need to develop a shared understanding of what 'spirituality' means and how it can be taught appropriately. As a highly secular country, these New Zealand findings are significant for medical education in other secular Western countries. Addressing spirituality with patients has been shown to positively impact a range of health outcomes, but how spirituality is taught in medical schools is still developing across the globe.